Digitalization in Administration Business : Opportunities and Challenges in the Technology Era - Arief Prayitno (Jurnal Sosial Sains dan Komunikasi, 2023)
Digitalization has become factor key in transformation administration business in the technology era. Research This aiming For analyze opportunities and challenges faced by the company in adopt digitalization in the administrative process business. The research method used is approach qualitative with technique studies literature and analysis descriptive. Research results show that digitalization give various opportunities, such as improvement efficiency operational, better data and information management accurate, improve experience customers, improve transparency and accountability, and speed up the decision-making process. Decision.. However, the implementation digitalization also faces challenges, such as gap technology, data security, change behavior consumers, high cost implementation, and development skills employees. Therefore that's the right strategy required For optimize benefit digitalization while mitigate the risks. This study expected can give outlook for perpetrator business in developing an effective digitalization strategy use increase Power compete in the technological era.